Necessity and feasibility of remote tele-programming of deep brain stimulation systems in Parkinson's disease - Esper, Christine D.; Merola, Aristide; Himes, Lyndahl; Patel, Neepa; Bezchlibnyk, Yarema B.; Falconer, Drew; Weiss, Daniel; Luca, Corneliu; Cheeran, Binith; Mari, Zoltan (Parkinsonism & related disorders, 2022)
Outcomes after deep brain stimulation (DBS) therapy are dependent on good surgical placement in the target nucleus and optimized stimulation parameters through multiple programming sessions. This often requires frequent travel to a specialized DBS center, which presents a challenge for those with limited access. Recently, the FDA approved a remote tele-programming solution for DBS. To determine if remote tele-programming of DBS systems is beneficial and useful for Parkinson's Disease (PD) patients, Parkinson's Foundation hosted a survey in collaboration with Abbott Labs. The survey was conducted to assess the need for telemedicine among PD patients with DBS and the usability of the telehealth interface for DBS teleprogramming. The survey included two validated instruments: The Effective Accessibility and Accommodation survey (EAA) and the Telehealth Usability Questionnaire (TUQ). 47 patients completed the EAA and 41 completed the TUQ. Results from the EAA revealed more than a third of PD patients cannot easily get to a clinic for various reasons, and more than a quarter reported difficulty contacting their clinic for advice. Results from the TUQ revealed overall satisfaction with the DBS remote programming telehealth interface and care provided. The majority of respondents reported that remote tele-programming visits are similar in quality to in-person visits. This study provides support for the use of telehealth and tele-programming for DBS management in PD patients. The ability to use remote technologies for care will increase access to DBS and mitigate the disparities that currently prevent access to care. •Surveyed PD patients with DBS to see if tele-programming is beneficial and useful.•More than a third of PD patients reported difficulty getting to a clinic.•More than a quarter reported difficulty contacting their clinic for advice.•Majority of PD patients reported overall satisfaction with remote tele-programming.•Supports the use of telehealth and tele-programming for DBS management in PD.